Advancing health education with telemedicine - López Cabrera, Mildred, 1987- (Medical Information Science Reference, 2022)
"This book provides relevant theoretical frameworks and the latest empirical research findings on how to leverage technologies and infrastructure of telehealth, telemedicine, and e-health to advance health professions education"--